The Influence of Corporate Governance on the Mitigation of Fraudulent Financial Reporting - Martins, Orleans S Silva (2020)
Purpose – This study analyzes the influence of the corporate governance structure in terms of mitigating the likelihood of fraudulent financial reporting (FFR) by firms in Brazil.   Design/methodology/approach – For this, we analyze the data of 314 publicly traded companies to estimate the likelihood of bankruptcy and the possibility of earnings manipulation, for subsequent identification of FFR.  Findings – Our results show that in 5.5% of cases there is an indication that FFR is likely, bankruptcy is predicted in 16.9% of cases, and the likelihood of earnings manipulation is identified in 17.7%. The corporate governance structure of the firms influences FFR mitigation, either directly or indirectly by reducing the chances of bankruptcy or earnings manipulation. We note that board-related governance practices are more effective against predicted bankruptcy, and audit-related practices are more related to reducing earnings manipulation.   Originality/value – The main contributions of this study lie in it identifying the probabilities of reporting fraud, bankruptcy, and earnings manipulation for companies in Brazil, as well as it verifying that corporate governance has been effective in mitigating these problems, either directly or indirectly. Thus, this information is useful for investors and regulators in this market.